O PRINCÍPIO DA MORALIDADE PÚBLICA NA ADPF Nº 347: REFLEXÕES SOBRE A CRISE DO SISTEMA PRISIONAL BRASILEIRO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present article aimd to study how the principle of public morality influences the achievement of the dignity of individuals serving sentences in correctional facilities. By evaluating the arguments presented by the ministers in the context of the Arguição de Descumprimento de Preceito Fundamental (ADPF) No. 347, it becomes evident that the conduction of public administrators in managing national prison policies does not adhere to moral standards. Various actions identified as causes of the Unconstitutional State of Things (Estado de Coisas Inconstitucional) in Brazilian prisons, such as insufficient allocation of financial resources, failure to meet basic health standards, and lack of provision for education, health, and legal assistance services, indicate a lack of ethical commitment from public administrators. To overcome the prison crisis, concrete measures that consider both legality and morality must be adopted to ensure that fundamental rights are effectively respected and that human dignity is placed at the center of public authority actions.